Development and validation of glycolysis‐related prognostic score for prediction of prognosis and chemosensitivity of pancreatic ductal adenocarcinoma. Issue 12 (3rd May 2021) - Zhang, Xiu‐Ping; Chen, Qinjunjie; Liu, Qu; Wang, Yang; Wang, Fei; Zhao, Zhi‐Ming; Zhao, Guo‐Dong; Lau, Wan Yee; Gao, Yu‐Zhen; Liu, Rong
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy with aggressive biological behaviour. Its rapid proliferation and tumour growth require reprogramming of glucose metabolism or the Warburg effect. However, the association between glycolysis‐related genes with clinical features and prognosis of PDAC is still unknown. Here, we used the meta‐analysis to correlate the hazard ratios (HR) of 106 glycolysis genes from MSigDB by the cox proportional hazards regression analysis in 6 clinical data sets of PDAC patients to form a training cohort, and a single group of PDAC patients from the TCGA, ICGC, Arrayexpress and GEO databases to form the validation cohort. Then, a glycolysis‐related prognosis (GRP) score based on 29 glycolysis prognostic genes was established in 757 PDAC patients from the training composite cohort and validated in 267 ICGC‐CA validation cohort (all P  < .05). In addition, including PADC, the prognostic value was also confirmed in other 7 out of 30 pan‐cancer cohorts. The GRP score was significantly related to specific metabolism pathways, immune genes and immune cells in the patients with PADC (all P  < .05). Finally, by combining with immune cells, the GRP score also well‐predicted the chemosensitivity of patients with PADC in the TCGA cohort (AUC = 0.709). In conclusion, this study developed a GRP score for patients with PDAC in predicting prognosis and chemosensitivity for PDAC.